2019
DOI: 10.1002/hbm.24826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the association between psychomotor processing speed and white matter hyperintensity: A comprehensive multi‐modality MR imaging study

Abstract: Cognitive processing speed is crucial for human cognition and declines with aging.White matter hyperintensity (WMH), a common sign of WM vascular damage in the elderly, is closely related to slower psychomotor processing speed. In this study, we investigated the association between WMH and psychomotor speed changes through a comprehensive assessment of brain structural and functional features.Multi-modal MRIs were acquired from 60 elderly adults. Psychomotor processing speeds were assessed using the Trail Maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…The microstructural integrity in the genu and splenium showed the highest significant relation with global cognitive function and executive functions, in the cingulum bundle with verbal memory performance ( Tuladhar et al, 2015 ). A recent multi-modality MRI study has shown that WMHs, combined with the disruption of passing-through fiber integrity and altered functional activities in areas connected by this fiber, are associated with a decline of psychomotor processing speed ( Wang et al, 2020a ). Moreover, the widespread WM microstructural impairments disrupt the large-scale distributed brain cognitive networks and underlie the various cognitive dysfunctions in ILA.…”
Section: Discussionmentioning
confidence: 99%
“…The microstructural integrity in the genu and splenium showed the highest significant relation with global cognitive function and executive functions, in the cingulum bundle with verbal memory performance ( Tuladhar et al, 2015 ). A recent multi-modality MRI study has shown that WMHs, combined with the disruption of passing-through fiber integrity and altered functional activities in areas connected by this fiber, are associated with a decline of psychomotor processing speed ( Wang et al, 2020a ). Moreover, the widespread WM microstructural impairments disrupt the large-scale distributed brain cognitive networks and underlie the various cognitive dysfunctions in ILA.…”
Section: Discussionmentioning
confidence: 99%
“…On a neurobiological level, reduced psychomotor speed is associated with reduced white matter integrity in several parts of the brain, such as corpus callosum and basal ganglia ( Karbasforoushan et al., 2015 ; Tsapanou et al., 2019 ; Wang et al., 2020 ). Such reduced white matter integrity may be induced by inflammation and peripheral cytokines ( Benedetti et al., 2016 ; Najjar and Pearlman, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, psychomotor speed is associated with reduced white matter integrity in magnetic resonance imaging (MRI) studies of healthy volunteers and patients with schizophrenia ( Karbasforoushan et al., 2015 ; Wang et al., 2020 ). This relation is prominent in several areas of the brain, including the basal ganglia ( Tsapanou et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recruited patients admitted to the Department of Neurology, the Second Affiliated Hospital, Zhejiang University School of Medicine, who received brain MRI and were diagnosed with CSVD between December 2015 and December 2020. More details about the cohort can be found in previously published studies (Wang et al ., 2020; Huang, Zhang, Jiaerken, Wang, Hong, et al ., 2021). Visual assessment of WMH presence (Fazekas scores) was performed by 2 neuroradiologists (R.Z.…”
Section: Methodsmentioning
confidence: 99%
“…The lesion prediction algorithm (LPA) of the Lesion Segmentation Toolbox (http://www.applied-statistics.de/lst.html) in SPM was used to automatically segment WMH lesions in the T2-FLAIR image of each subject under study. Previous studies (Cedres et al ., 2020; Vanderbecq et al ., 2020; Wang et al ., 2020; Zhang et al ., 2021) have shown successful applications of the LPA algorithm in WMH segmentation using T2-FLAIR. Each segmented result was visually inspected and manually corrected by expert readers (S.W.…”
Section: Methodsmentioning
confidence: 99%